2020
DOI: 10.1038/s41598-020-76846-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and bother of lower urinary tract symptoms and overactive bladder in Poland, an Eastern European Study

Abstract: The prevalence of lower urinary tract symptoms (LUTS) and overactive bladder (OAB) has been measured by population-based investigations in many parts of the world. However, data are lacking for Eastern Europe, and there has not been any large population-representative study in any country of this region. Therefore, the aim of this study was to evaluate the prevalence and associated bother of LUTS and OAB in a population-representative sample of persons aged ≥ 40 years in Poland. This investigation was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 37 publications
4
52
0
1
Order By: Relevance
“…Because validated instruments measure relevant symptom burden, they may be more optimal for population-based analyses than rigid classification systems based only on symptom prevalence [19]. Therefore, we used the OAB-V8 questionnaire, which is characterized by high sensitivity and specificity in recognizing OAB [19], and it is used widely as a valid screening tool to estimate OAB prevalence in large population-based analyses [9]. We also did not collect data regarding causes of treatment discontinuation and drug-related adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because validated instruments measure relevant symptom burden, they may be more optimal for population-based analyses than rigid classification systems based only on symptom prevalence [19]. Therefore, we used the OAB-V8 questionnaire, which is characterized by high sensitivity and specificity in recognizing OAB [19], and it is used widely as a valid screening tool to estimate OAB prevalence in large population-based analyses [9]. We also did not collect data regarding causes of treatment discontinuation and drug-related adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a further analysis of data from the LUTS POLAND survey, population-representative cross-sectional epidemiological study. Complete details of the study design and methodology are published and presented briefly here [9]. The study included representative pools of men and women, aged ≥ 40 years, who lived in all geographical regions of Poland (including urban and rural areas).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study included representative pools of men and women aged ≥ 40 years living in all geographical regions of Poland (including urban and rural areas with appropriate proportions). We described the justification for this recruitment approach and the details of the survey and study design elsewhere [ 5 ]. The Ethics Committee of Jagiellonian University Medical College, Krakow, Poland (1072.6120.160.2019) approved the study.…”
Section: Methodsmentioning
confidence: 99%
“…LUTS were found to affect up to 74% of adults aged ≥ 40 years in Europe and North America [ 2 ], 75% in South America [ 3 ], and 61% in Asia [ 4 ]. In a recent population-representative epidemiological study of LUTS in Poland, the first reliable and nationwide epidemiological study of LUTS in an Eastern European country, we reported LUTS prevalence of 69.8% in adults aged ≥ 40 years, with more women affected than men (72.6% vs. 66.2%) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%